BEST EXAMPLE OF POLLUTION FREE CITY PLANNING: HARAPPAN CIVILIZATION: प्रदूषण मुक्त नगर नियोजन का उत्कृष्टतम उदाहरण: हड़प्पा सभ्यता - Pandey, Preeti (International Journal of Research -GRANTHAALAYAH, 2015)
At present the whole world suffers from environmental problems. These problems appear everywhere in the form of pollution. Pollution, which has a harmful effect on the physical, chemical and biological properties of our environment or biosphere, is called pollution. For a few decades, the natural climate has seen astonishing changes like flooding has started where there was a drought. High rainfall areas are becoming drought-prone. Pollution is the increase in the temperature of the earth, disintegration in the quality of water bodies due to acid rain and imbalance in the natural air structure. Various types of pollution stand before us due to unnecessary experiments with natural sources. It is the duty of mankind to find and eliminate the factors of pollution. Various efforts are being made to resolve these problems. Scientists, environmental thinkers, government and non-government are all trying to see how a civilization of history can be seen as a means to solve this problem. How the people of that civilization were aware of pollution and what measures were being taken in their city planning to deal with air and water pollution. It is worth watching. The name of the civilization is the Indus-Saraswat civilization, often known as the Harappan civilization. In the northwestern part of India, this very developing civilization emerged on the banks of the Indus and Saraswati rivers. It was the first urban civilization of India which was of a higher quality than the European metropolises of the present day. Archaeologist John Marshall says that nothing can match the grand baths and open houses of the inhabitants of Mohenjodaro, neither in archaeological Egypt, nor in Mesopotamia, nor in any other country in West Asia. In those countries, most of the attention and resources were spent on building temples and royalty and mausoleums, while the common man had to be satisfied with only a few rough houses. The Indus Valley Civilization has a contrasting view. The most important constructions here were those built for the convenience of the townspeople, such as collective and private baths, the excellent drainage system found at Mohenjodaro which is the first of its kind as far as possible. वर्तमान में पर्यावरणीय समस्याओं से सम्पूर्ण विश्व ग्रस्त है। ये समस्यायें प्रदूषण के रूप में सर्वत्र दिखाई देती हैं। हमारे पर्यावरण अथवा जीवमण्डल के भौतिक, रासायनिक एवं जैविक गुणों के ऊपर जो हानिकारक प्रभाव पड़ता है, प्रदूषण कहलाता है। कुछ दशकों से प्राकृतिक जलवायु में विस्मयकारी परिवर्तन होने लगे हैं जैसे जहाँ सूखा होता था वहाँ बाढ़ आने लगी है। अतिवृष्टि वाले क्षेत्र सूखाग्रस्त होने लगे हैं। धरती के तापमान में वृद्धि, अम्लीय वर्षा के फलस्वरूप जलस्रोतों की गुणवत्ता में विघटन तथा प्राकृतिक वायु संरचना में असंतुलन ही प्रदूषण है। प्राकृतिक स्रोतों के साथ अनावश्यक प्रयोगों के कारण विभिन्न प्रकार के प्रदूषण हमारे सम्मुख खड़े हैं। प्रदूषण के कारकों को ढूँढ़कर इन्हें समाप्त करना ही मानव जाति का कत्र्तव्य है। इन समस्याओं के निवारण हेतु विभिन्न प्रयास किये जा रहे हैं। वैज्ञानिक, पर्यावरण चिंतक, सरकारी एवं गैर-सरकारी सभी यह प्रयास कर रहे हैं कि किस प्रकार इस समस्या के समाधान के रूप में इतिहास की एक सभ्यता को साधन के रूप में देखा जा सकता है। किस प्रकार उस सभ्यता के लोग प्रदूषण के प्रति जागरूक थे और वायु तथा जल प्रदूषण से निपटने के लिये अपने नगर नियोजन में क्या-क्या उपाय कर रहे थे। यह देखने योग्य है। सभ्यता का नाम है सिन्धु-सारस्वत सभ्यता जिसे प्रायः हड़प्पा सभ्यता के नाम से जानते हैं। भारत के पश्चिमोत्तर भाग में सिन्धु एवं सरस्वती नदी के तट पर इस अत्यन्त विकासशील सभ्यता का उदय हुआ। यह भारत की प्रथम नगरीय सभ्यता थी जो कि वर्तमान समय के यूरोपीय महानगरों से भी अधिक उच्च कोटि की थी। पुरातत्त्ववेत्ता जाॅन मार्शल का कहना है कि न तो पुराऐतिहासिक मिस्त्र में, न मेसोपोटामिया में और न पश्चिम एशिया के किसी अन्य देश में ही कुछ भी मोहनजोदड़ो के निवासियों के भव्य स्नानागारों और खुले-खुले घरों की बराबरी नहीं कर सकता है। उन देशों में अधिकतर ध्यान और साधन देवमंदिरों और राजप्रसादों तथा समाधियों के निर्माण पर व्यय किया जाता था जबकि सामान्य जन को मामूली कच्चे घरों से ही संतोष कर लेना पड़ता था। सिंधु घाटी सभ्यता में इसके विपरीत दृश्य है। यहाँ सबसे महत्त्वपूर्ण निर्माण थे वे जो नगरवासियों के सुविधार्थ बनाये गये थे, जैसे सामूहिक और निजी स्नानागार, मोहनजोदड़ों में प्राप्त उत्कृष्ट जलनिकास प्रणाली जो जहाँ तक है अपने प्रकार की पहली हैं।